Portable devices and mobile instruments for infectious diseases point-of-care testing. (4th May 2017) - Bissonnette, Luc; Bergeron, Michel G.
ABSTRACT: Introduction : Rapidity, simplicity, and portability are highly desirable characteristics of tests and devices designed for performing diagnostics at the point of care (POC), either near patients managed in healthcare facilities or to offer bioanalytical alternatives in external settings. By reducing the turnaround time of the diagnostic cycle, POC diagnostics can reduce the dissemination, morbidity, and mortality of infectious diseases and provide tools to control the global threat of antimicrobial resistance. Areas covered : A literature search of PubMed and Google Scholar, and extensive mining of specialized publications, Internet resources, and manufacturers' websites have been used to organize and write this overview of the challenges and requirements associated with the development of portable sample-to-answer diagnostics, and showcase relevant examples of handheld devices, portable instruments, and less mobile systems which may or could be operated at POC. Expert commentary : Rapid (<1 h) diagnostics can contribute to control infectious diseases and antimicrobial resistant pathogens. Portable devices or instruments enabling sample-to-answer bioanalysis can provide rapid, robust, and reproducible testing at the POC or close from it. Beyond testing, to realize some promises of personalized/precision medicine, it will be critical to connect instruments to healthcare data management systems, to efficiently link decentralized testing results to the electronic medical record of patients.